Development of mobile product sharing and search system (Part I) - Chia, Ming En (2014)
As technology advances, mobile devices these days are getting smarter. It includes wide range of sensors and components that do not exist in traditional PC. In recent years, the global sales of smartphone outpacing those of laptop and desktop have resulted in an increase in smartphone users. Besides, E-commerce industry has also experienced stable growth throughout the years. Since 2011, the worldwide Business to Consumer (B2C) sales have increased by nearly 200 billion each year and this trend is expected to continue.